Meningkatkan Keterampilan Berkomunikasi Melalui Metode Bercerita dengan Alat Peraga Wayang pada Anak Kelompok B TK Dwijorini Tretep - Sri Kustianawati (Universitas PGRI Semarang, 2020)
This class action research was carried out because of a problem that occurred in Group B TK Dwijorini Tretep's children, namely the low communication skills of children. The purpose of this study was to determine the application of the method of telling stories with puppets and to find out the percentage increase in communication skills of the children of Group B Kindergarten Dwijorini Tretep Temanggung Semester I of the Academic Year 2017/2018 after applying the method of telling stories with puppets. The subjects of this study were the students of Group B TK Dwijorini Tretep with 24 children. The research was carried out in November 2017. Data collection methods used were observation, documentation and interviews. Based on the results of the study, it can be concluded that through the method of storytelling using puppet props has proven to be effective in improving the communication skills of children in Group B TK Dwijorini Tretep Temanggung. In the initial condition, only 5 children (20.9%) of the 24 children who had communication skills developed as expected, Improved in Cycle I, 13 children (54.1%) received underdeveloped assessment, started to develop 5 children ( 20.9%), developed according to the expectations of 6 children (25%). After the improvement in Cycle II, children who received underdeveloped assessment 1 child (4.3%), started to develop 2 children (8.2%), developed as expected 18 children (75%), developed very well 3 children (12, 5%) and have reached the set standard of mastery learning that is the child is able to answer more complex questions, the child has more words to express ideas to others, the child is able to communicate verbally, has a vocabulary, the child is able to continue part of the story that has been played.